First Trimester Screening – Current Status and Future Prospects After Introduction of Non-invasive Prenatal Testing (NIPT) at a Tertiary Referral Center - Walter, Adeline; Simonini, Corinna; Gembruch, Ulrich; Flöck, Anne; Strizek, Brigitte; Geipel, Annegret (Geburtshilfe und Frauenheilkunde, 2022)
Objective To investigate the uptake of different components of first trimester screening (FTS) and the impact on invasive diagnostic testing (IPT) since the introduction of non-invasive prenatal testing (NIPT) at a level III center.Methods Retrospective data analysis was conducted for singleton pregnancies that presented for FTS between 01/2019–12/2019 (group 1, n = 990). Patients were categorized into three risk groups: low risk for trisomy 21 (< 1 : 1000), intermediate risk (1 : 101–1 : 1000) and high risk (≥ 1 : 100). Uptake of NIPT and IPT was analyzed for each of the risk groups. Results were compared to a previous cohort from 2012/2013 (immediately after the introduction of NIPT, group 2, n = 1178).Results Group 1 showed a significant increase in the use of NIPT as part of FTS (29.5% vs. 3.7% for group 2, p = 0.001) in all three risk groups. Overall IPT rates were lower in group 1 (8.6%) vs. group 2 (11.3%, p = 0.038), mainly due to a significant reduction of IPT in the intermediate risk group. IPT rates in the high-risk group remained stable over time.Conclusion Appropriate clinical implementation of NIPT is still currently a challenge for prenatal medicine experts. Our data suggest that widespread uptake of NIPT is becoming more common these days; however, a contingent approach might prevent redundant uptake.
Keywords: NIPT; zellfreier fetaler DNA-Test; Ersttrimesterscreening; pränatale Beratung